تحديد مؤشرات الأداء الأكثر ملاءمة لمتابعة وتحسين أداء مشاريع التشييد في سورية - ميـّــا رنـــــا; أحمد ليال هيثم (Latakia University Journal -Engineering Sciences Series, 2014)
خلق النمو الاقتصادي, والتنافسية العالية ضغطاً كبيراً على شركات التشييد لتحسين إنتاجيتهم وأدائهم. وأجريت العديد من الدراسات حول قياس الأداء على مستوى المشروع, ومؤخراً ازداد الطلب والحاجة لتقييم الأداء على مستوى الشركة. يهدف هذا البحث إلى تعيين مجموعة من مؤشرات الأداء الرئيسة KPIS, حيث تم إعداد قائمة بـ 20 مؤشراً محتملاً للأداء وفق BSC وذلك من خلال إجراء تحليل كمي ونوعي وتم الحصول على المعلومات المطلوبة حول الأهمية النسبية للمؤشرات من خلال إجراء مقابلات مع ستة خبراء في صناعة التشييد لتحديد حجم الأهمية النسبية لكل مؤشر, على اعتبار أن العدد الكبير من مؤشرات الأداء يصعب قياسه والسيطرة عليه, وقد اعتمدنا في ذلك على طريقة التحليل الهرمي AHP لتحديد عدد أقل وأكثر فعالية من مؤشرات الأداء. واستخدم لتحليل مجموعة الإجابات برنامج خيار الخبيرExpert Choice . وحصلنا بنتيجة ذلك على 9 مؤشرات هامة (مفتاحية), والتي يمكن أن تستخدم مباشرة كمؤشرات مفتاحية لقياس وتحديد أداء المشاريع أو كمؤشرات مفتاحية ضمن نظام متكامل لقياس وتتبع الأداء يساعد في تحسين أداء مشاريع التشييد في سورية. Economic growth and high competition have put a strong pressure on construction companies to improve their productivity and performance. Many studies on performance measurement have been carried out at the project level. Recently, the demand for performance evaluation at the company level has increased. This paper aims to identify a set of Key Performance Indicators (KPIs). A List of 20 potential performance indicators has been identified according to Balance Score Card (BSC) through a quantitative and qualitative analysis. We have obtained the required information about the relative importance of the indicators through interviews with six experts in the construction industry to determine the size of the relative importance of each indicator, on the grounds that a large number of performance indicators are difficult to measure and control. We have adopted the Analytic Hierarchy Process (AHP) to identify fewer and more effective performance indicators. And we have used Expert Choice software to analyze expert answers. As a result, we have obtained 9 important indicators which can be directly used as indicators to measure and identify performance projects or as indicators within an integrated system, for performance measurement and tracking helps in improving the performance of construction projects in Syria.